Heterocyclization of allyl substituted chloromethyloxiranes with anhydrous gaseous HCl - Cansiz, A; Servi, S; Coskun, M; Ahmedzade, M (Editura Academiei Romane, 2000)
The heterocyclization of allyl substituted chloromethyloxiranes with anhydrous gaseous HCl at room temperature gives 2-chloroalkyl-3-chloro-5,5-dialkyltetrahydrofurans, which are important building units for the synthesis of biologically active compounds.
Keywords: Intramolecular Cyclization; Alcohols